An approach to reusable software for mobile robot applications through analysis patterns - Jawawi, Dayang N. A. (2005)
The use of software analysis patterns as a means to facilitate Autonomous mobile robots (AMR) software knowledge reuse through component-based software engineering is proposed. The software analysis patterns for AMR were obtained through a pattern mining process, and documented using a standard catalogue template. These analysis patterns are categorized according to hybrid deliberate layered architecture of robot software: reactive layer, supervisor layer and deliberative layer. In this paper, the analysis patterns in the reactive layer are highlighted and presented. The deployment of the analysis patterns are illustrated and discussed using an AMR software case study. The reuse potential of these patterns is evaluated by measuring the reusability of components in the analysis patterns.